Increase Breast Milk Production for Postpartum Mothers with Oxytocin Massage Using Innovative Massage Tools - Istighosah, Nining; Sari, Aprilia Nurtika (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Goal 3 of Global commitment of 2015-2030 Sustainable Development Goals (SDGs) program is to ensure a healthy life and to promote well-being for all people at all ages in the 2nd achievement indicator targeting by 2030. It is hoped to end infant and under-five mortality that can be avoided, with all countries trying to reduce the Neonatal Mortality Rate to at least 12 per 1,000 KH and the Toddler Mortality Rate by 25 per 1,000 KH. Infant mortality cases caused by nutritional factors reached 53%. Several diseases that arise due to malnutrition include pneumonia (13.2%), diarrhea (17.2%) and perinatal problems (36%). Breast milk is the best food for babies and has the right balance of nutrients, is bioavailable, easy to digest, protects babies from disease, and has anti-inflammatory properties. This study aims to analyze the difference in the volume of breast milk before and after the mother received oxytocin massage with the Effleurage technique and a combination of innovative massage tools. Subjects and Method: This research is a quasi experiment. The study was conducted in the City of Kediri from August to September 2020. The sample used was post partum women on days 4 to 10 using simple random sampling technique. The dependent variable is the volume of breast milk. The independent variable is the type of oxytocin massage treatment with effleurage technique, and the combination of oxytocin massage with efflurage technique and innovative massage tools. Data analysis per treatment and control groups used the one-way annova test with 95% CI. Results: There was no difference in the mean volume of breast milk in mothers who received lactation massage using the innovative massage method (Mean= 21.65; SD= 15.43; p= 0.994), conventional Efflurage massage (Mean= 22.15; SD= 15.43; p= 0.330), and in control group (Mean= 20.50; SD= 15.43; p=0.386). Conclusion: There was no difference in the mean volume of breast milk in each group and this result was not statistically significant.